EXPLORING NEW SOURCES OF ANTIOXIDANTS AND PHENOLIC CONTENTS FROM A MARINE RED ALGA AGARDHIELLA ROBUSTA (GREVI.) BORG. COLLECTED FROM KARACHI COAST - U. Hanif; B. Ghazala; S. Farid; A. A. Farooqi (Journal of Animal and Plant Sciences, 2016)
The antioxidant potential and total phenolic contents of a red alga Agardhiella robusta (Grevi.) Borg belonging to Rhodophycota  collected from coastal areas of  Karachi, Pakistan was investigated through various in vitro protocols. Antioxidant potential measured through total antioxidant determination, total phenolic contents, ferric reducing antioxidant power (FRAP) and DPPH analysis. The antioxidant components were initially extracted in methanol and were further fractionated in solvents of different polarity. The results showed that the petroleum ether fraction exhibited highest DPPH radical scavenging activity, i.e. (79.5±1.9%) at a concentration of 1000ug/ml with IC50 286.13±0.34 µg/mL relative to the BHT. While Methanol extract showed highest  phenolic contents i.e. 1542.5 ±1.2 GAEmg/mL, highest FRAP values i.e. 18.95± TEuM/mL as well as least IC50 value of 25.81 ± 0.65 μg/mL which indicated its potential for scavenging the free radicals. On the basis of these results obtained here Agardhiella robusta (Grevi.) Borg considered as a rich source of  antioxidant.
Keywords: Antioxidants; Agardhiella robusta; total phenolic contents; ferric reducing antioxidant power (FRAP) and DPPH